THE NEED FOR DIVERSITY AND MANAGEMENT EFFICIENCY - A. V. Raychenko (Вестник университета)
The publication presents primary materials and intermediate conclusions of the author`s fundamental research aimed at establishing a correlation between the diversity and effectiveness of management organization. The relevance of identifying this ratio increases dramatically with the development and implementation of digitalization management programs, which inevitably formalize, unify and ultimately limit the allocation, mobilization and use of impact resources. The most contrasted studied relationships are distinguished, analysed and evaluated using examples of the development and implementation of crisis management strategies and tactics, which are manifested in clear and widely discussed situations of domestic and foreign practice in the development, adoption and implementation of targeted impacts. The publication presents a statement of the problem, the study and solution of which is offered by it for a wide and diverse discussion in the professional scientific environment.